What can Written-Words Tell us About Lexical Retrieval in Speech Production? - Navarrete, Eduardo; Mahon, Bradford Z.; Lorenzoni, Anna; Peressotti, Francesca (Frontiers in Psychology, 2016)
In recent decades, researchers have exploited semantic context effects in picture naming tasks in order to investigate the mechanisms involved in the retrieval of words from the mental lexicon. In the blocked naming paradigm, participants name target pictures that are either blocked or not blocked by semantic category. In the continuous naming task, participants name a sequence of target pictures that are drawn from multiple semantic categories. Semantic context effects in both tasks are a highly reliable phenomenon. The empirical evidence is, however, sparse and inconsistent when the target stimuli are printed-words instead of pictures. In the first part of the present study we review the empirical evidence regarding semantic context effects with written-word stimuli in the blocked and continuous naming tasks. In the second part, we empirically test whether semantic context effects are transferred from picture naming trials to word reading trials, and from word reading trials to picture naming trials. The results indicate a transfer of semantic context effects from picture naming to subsequently read within-category words. There is no transfer of semantic effects from target words that were read to subsequently named within-category pictures. These results replicate previous findings (Navarrete, Mahon, Caramazza, 2010) and are contrary to predictions from a recent theoretical analysis by Belke (2013). The empirical evidence reported in the literature together with the present results, are discussed in relation to current accounts of semantic context effects in speech production.